Sphingosine 1-phosphate-induced ICAM-1 expression via NADPH oxidase/ROS-dependent NF-kappaB cascade on human pulmonary alveolar epithelial cells - Chin-Chung eLin; Chien-Chung eYang; Chien-Chung eYang; Rou-Ling eCho; Chen-yu eWang; Li-Der eHsiao; Chuen-Mao eYang; Chuen-Mao eYang; Chuen-Mao eYang (Frontiers Media S.A., 2016)
The intercellular adhesion molecule-1 (ICAM-1) expression is frequently correlated with the lung inflammation. A bioactive sphingolipid metabolite, sphingosine-1-phosphate (S1P), was involved in inflammation through the adhesion molecules induction, and then caused lung injury. However, the transduction mechanisms of the S1P stimulation to induce ICAM-1 expression in human pulmonary alveolar epithelial cells (HPAEpiCs) remain unclear. Here, we demonstrated that exposure of HPAEpiCs to S1P significantly induces ICAM-1 expression leading to increase monocyte adhesion on the surface of HPAEpiCs. These phenomena were effectively attenuated by pretreatments with series of inhibitors such as Rottlerin (PKCdelta), PF431396 (PYK2), diphenyleneiodonium chloride (DPI), apocynin (NADPH oxidase), Edaravone (ROS), and Bay11-7082 (NF-kappaB). Consistently, knockdown with siRNA transfection of PKCdelta, PYK2, p47phox, and p65 exhibited the same results. Pretreatment with both Gq-coupled receptor antagonist (GPA2A) and Gi/o-coupled receptor antagonist (GPA2) also blocked S1P-induced ICAM-1 protein and mRNA expression. We observed that S1P induced PYK2 activation via a Gq-coupled receptor/PKCdelta-dependent pathway. In addition, S1P induced NADPH oxidase activation and intracellular ROS generation, which were also reduced by Rottlerin or PF431396. We demonstrated that S1P induced NF-kappaB p65 phosphorylation and translocation from the cytosol to the nucleus in HPAEpiCs, which was inhibited by Rottlerin, PF431396, APO, DPI, or Edaravone. In the in vitro study, we established that S1P induced monocyte adhesion via an ICAM-1-dependent pathway. In the in vivo study, we found that S1P induced ICAM-1 protein and mRNA levels in the lung fractions, pulmonary hematoma, and leukocyte (mainly eosinophils and neutrophils) count in bronchoalveolar lavage (BAL) fluid in mice via a PKCdelta/PYK2/NADPH oxidase/ROS/NF-kappaB signaling pathway. We concluded that S1P may induce lung inflammation via ICAM-1 induction associated with leukocyte recruitment.